Comparative Study of Web Page Ranking Algorithms - Santosh Kumar, Chirag Anand (International Journal of Advanced Science and Technology, 2020)
Internet is the most of the important service and prime source of information now a day. Every one has access to it even through their smart devices. For getting any type of information people rely on web for their required information. In today’s situation it’s service provider’s duty to provide relevant, accurate and point to point information to their users according to their query posed. But the rapid increase in the quantity of information has made it difficult to provide the relevant information by using the contents of the webpage and hyperlinks among the web pages. This paper deals with the comparison & analysis of web page ranking algorithms arranged on different parameters. Several search engines also try to increase the accuracy information retrieval. A Comparative study has been done based on the different logic of web page ranking algorithms for their limitations and strengths for finding out the future scope.